2019
DOI: 10.3389/fimmu.2019.00945
|View full text |Cite
|
Sign up to set email alerts
|

Functional Roles of the IgM Fc Receptor in the Immune System

Abstract: It is now evident from studies of mice unable to secrete IgM that both non-immune “natural” and antigen-induced “immune” IgM are important for protection against pathogens and for regulation of immune responses to self-antigens. Since identification of its Fc receptor (FcμR) by a functional cloning strategy in 2009, the roles of FcμR in these IgM effector functions have begun to be explored. Unlike Fc receptors for switched Ig isotypes (e.g., FcγRs, FcεRs, FcαR, Fcα/μR, pIgR, FcRn), FcμR is selectively express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(81 citation statements)
references
References 94 publications
(154 reference statements)
2
75
3
1
Order By: Relevance
“…An early IgM response may be protective because of its pentameric structure which results in high-affinity antibodies which can neutralise viruses before the development of an IgG response [38]. IgM also plays an important role in the maturation of B-cell responses regulating B-cell tolerance as well as class switching to IgG and IgA [40,79]. Results of this study are in keeping with those of vaccination studies in HIV, which showed that subjects with a higher anti-envelope IgA:IgG ratio after vaccination were more likely to become infected, potentially indicating reduced protective immunity [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An early IgM response may be protective because of its pentameric structure which results in high-affinity antibodies which can neutralise viruses before the development of an IgG response [38]. IgM also plays an important role in the maturation of B-cell responses regulating B-cell tolerance as well as class switching to IgG and IgA [40,79]. Results of this study are in keeping with those of vaccination studies in HIV, which showed that subjects with a higher anti-envelope IgA:IgG ratio after vaccination were more likely to become infected, potentially indicating reduced protective immunity [43].…”
Section: Discussionmentioning
confidence: 99%
“…IgM was shown to be critical for protection against West Nile virus and human immunodeficiency virus (HIV) mucosal transmission [35,36], where the pentameric structure of IgM is proposed to have high avidity resulting in a slow or absent off rate [35,37]. IgM was also shown to have neutralising properties against chikungunya and influenza viruses [36,38,39] and an important role in early immune activation via its Fc portion [40]. Furthermore, an early neutralising IgM response is induced by the smallpox (vaccinia) vaccine, one of the most successful vaccines to date [38,41].…”
Section: Introductionmentioning
confidence: 99%
“…The FCMR gene codes for an immunoglobulin receptor that is highly selective for IgM and can contribute to B cell activation [ 32 , 33 ]. However, the biologic role of FCMR in both normal and neoplastic B cells has not been fully understood [ 56 ]. Mouse models have shown that FCMR knock-down B cells have increased germinal center formation and reduced class switch and generation of Ag-specific plasma cells [ 45 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…These data would suggest a positive regulation by FCMR on ABC-DLBCL signaling, data fitting with the reported reduced tonic BCR signaling in FCMR-deficient mice [ 60 ]. However, the definition of the role of FCMR in normal and malignant B cells, especially in ABC-DLBCL, will need further studies [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, most of the biological activity of various classes of Abs is mediated through interactions between the Fc domain and Fc receptors, while additionally involving other receptors [ 28 , 31 ]. Five Fc receptors for IgG (FcγR), two Fc receptors for IgE (FcεR), one for IgA (FcαR) and for IgM (FcμR), as well as for IgA and IgM (FcRα/μR), were identified in humans [ 12 , 16 , 28 ]. The diversity of Fc domains further extends Ig functions due to the presence of sequence polymorphisms and variations in the glycosylation patterns [ 32 , 33 ].…”
Section: Canonical and Non-canonical Functions Of Immunoglobulinsmentioning
confidence: 99%